2021
DOI: 10.3390/biology10080784
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Biohazardous Dye Brilliant Blue R Using Organometallic Silver Nanoparticles Synthesized through a Green Chemistry Method

Abstract: Nowadays, nanostructures having tremendous chemical and physical properties are gaining attention in the biomedical industry. However, when they are prepared through classical methods (physical and chemical), they are often non-biocompatible and toxic. Considering the mentioned factors, in this research, organometallic silver nanostructures (OMAgNs) have been prepared by the green chemistry method using the acetone, methanol, and methanol-hexane-based extracts of the medicinally important plant Cichorium intyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…47,48 Chloride (Cl À ) anions are macronutrients that significantly exist in plants contributing to maintaining photosynthesis and homeostatis. 49 Generally, other elements observed by EDX analysis including carbon, oxygen, and chloride were demonstrated as capping agents of the biosynthesized silver nanoparticles in agreement with other studies. 50,51 The elemental mapping of the biosynthesized AgNPs is presented in Fig.…”
Section: Paper Materials Advancessupporting
confidence: 90%
“…47,48 Chloride (Cl À ) anions are macronutrients that significantly exist in plants contributing to maintaining photosynthesis and homeostatis. 49 Generally, other elements observed by EDX analysis including carbon, oxygen, and chloride were demonstrated as capping agents of the biosynthesized silver nanoparticles in agreement with other studies. 50,51 The elemental mapping of the biosynthesized AgNPs is presented in Fig.…”
Section: Paper Materials Advancessupporting
confidence: 90%
“… 34 Moreover, the X-ray emission from the enzymes and proteins present in the aqueous extract of H. sabdariffa flowers resulted in the detection of other elements as silicon, chlorine, carbon, and oxygen. 35 In addition, the abundance of chlorine (Cl − ) ions in plants, which were found to be responsible for maintaining homeostasis and playing a crucial role during photosynthesis, was signified by other researchers as the reason for the strong peak of Cl− detected by EDX spectrum of the biogenic AgNPs. 36 Communally, the odd elements as Si, and Cl apprehended by EDX elemental configuration were reported to be crucial for the bioreduction of Ag + ions to synthesize elemental silver (Ag 0 ), as well as for capping and stabilizing the biosynthesized AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Kasaai [104] found that the incorporation of nano-Si as a surface coating in food packaging increases the quality and storage ability of horticultural crops. Ag-NPs coated packaging materials can lessen the microbial activity, leading to an increase shelf-life of food materials [105]. Besides, Ag-NPs, ZnO-NPs, TiO 2 -NPs, MgO-Nps, CuO, chitosan nanoparticles, carbon nanotubes, quantum dots, etc., are commercially very important for improving the quality and shelf-life of storage fruits, vegetables and exporting foods, since these NPs have anti-microbial activity [102,[106][107][108].…”
Section: Nanofilm/coating Component Beneficial Effect On Fruit Fruit Referencementioning
confidence: 99%
“…The inclusion of Ag-nanostructures in coating organic polymers augmented the mechanical properties of coating films [115]. Like India, China is also widely applying Ag-NPs to boost the storage and freshness of fruits and vegetables [105]. Owing to the significant antimicrobial characteristics of Ag-NPs, the shelf-life of cherry tomatoes can be enhanced by up to 15 days.…”
Section: Silver (Ag) Nanoparticlesmentioning
confidence: 99%